Thai -Journal Citation Index (TCI) centre: 10 years of experiences, lessons learned, and ongoing development - Narongrit, Sombatsompop; Srichan, Chancheewa; Teerasak, Markpin; Nongyao, Premkamolnetr; Santi, Ittiritmeechai; Chatree, Wongkaew; Wutthisit, Yochai; Preeyanuch, Ratchatahirun (Malaysian Journal of Library and Information Science, 2017)
This paper outlines 10 years of experiences concerning the inception and operation of the Thai- Journal Citation Index (TCI) Centre, which was the first national citation centre in Thailand and also in the Association of Southeast Asian Nations (ASEAN), founded in 2001. The experiences discussed involve the aims and missions of the TCI towards improving the quality and increasing the visibility of local and national research findings. The impacts of the TCI on the academic community are also described, together with the challenges faced in regard to its acceptability, especially by internationally oriented researchers. Various TCI activities to promote and disseminate national research findings are discussed, such as a quality assessment program for Thai journals indexed in TCI, awarding high-quality Thai journals, launching the Thai Journal Online (Thai-JO) system, and identification and comparison of local research performances using TCI and international databasesm as data sources. Finally, the ASEAN Citation Index (ACI) database is introduced, as part of the preparation for the ASEAN Economic Community (AEC) in conjunction with the TCI and other national citation index databases, in order to enhance the dissemination and quality of ASEAN research profiles on an international platform.